1979
DOI: 10.1002/bjs.1800660407
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolites and nitrogen balance after abdominal surgery in man

Abstract: The relation of lipid metabolism to nitrogen balance was studied in patients having undergone abdominal surgery and was compared with control subjects who had fasted for a similar period. The patients had lower circulating concentrations of glycerol, non-esterified fatty acids and ketone bodies. There were inverse correlations between blood alanine and ketone body concentrations in both patients (r = -0.64, P less than 0.01) and controls (r = -0.58, P less than 0.01). Nitrogen excretion by patients (12.7 mmol/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2

Year Published

1979
1979
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 31 publications
2
14
2
Order By: Relevance
“…The discrepancy with the present data could relate to species differences in hormone action on the liver (Bahnsen et al, 1984) and the more severe stress during sepsis. On the other hand a decreased ketone body response to fasting has also been noted in human subjects following operation (Foster et al, 1979).…”
Section: Discussionmentioning
confidence: 88%
“…The discrepancy with the present data could relate to species differences in hormone action on the liver (Bahnsen et al, 1984) and the more severe stress during sepsis. On the other hand a decreased ketone body response to fasting has also been noted in human subjects following operation (Foster et al, 1979).…”
Section: Discussionmentioning
confidence: 88%
“…These differences deserve further investigation, including other hormones such as growth hormone and catecholamines, and other metabolites over a long time interval, as some disturbances of metabolism may be long lasting. 6 The problems of the stress response may be countered by the use of new opiate partial agonists and opioid peptide analogues rather than the more perilous applications of extreme doses of agonist drugs or the uncommon practice of very extensive extradural analgesia. Buprenorphine, for instance, appears to offer a safer approach to the goal of reducing the problems associated with surgical stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have shown that the levels range from no change to a mild elevation to a substantial increase. [225][226][227][228] It has been demonstrated that patients who remain normoketonemic after major surgery are likely to manifest an increased nitrogen loss in comparison with patients who are hyperketonemic postoperatively.169 Studies in trauma patients suggest that the lack of ketogenesis is due to postinjury vasopressin release, the degree of which is directly proportional to the severity of injury.214, 220 Therefore, vasopressin may exacerbate protein catabolism and muscle wasting by suppressing ketogenesis in patients subjected to severe trauma, major surgical stress, or sepsis.…”
Section: Metabolismmentioning
confidence: 99%